Evaluating the year 2000 project a management guide for determinting reasonable care - Braithwaite, Timoyhy (John Wiley & Sons, 1998)
Computer and network failures, massive data corruption, loss of revenue, improper product dating, government fines, litigation by stockholders, partners, employees, clients, suppliers. . . . With so much at stake, you simply cannot afford to delegate the responsibility for dealing with the Year 2000 computer crisis to your IT managers or outside consultants. Legally and ethically, it is your job to guarantee that your organization takes all the necessary steps to avert disaster. And time is running out. If you don't have the problem in hand soon, you may be too late.